Moringa Leaves as an Alternative Food in Efforts to Prevent Stunting: A Literature Review - Sari, Rati Purnama (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2022)
Stunting is a growth and development disorder where the condition of the child is shorter than his age. Indonesia is still one of the countries with a high prevalence of stunting under five in Southeast Asia. Prevention of stunting requires efforts to fulfill nutrition in the First 1000 Days of Life (HPK) from pregnant women to babies aged 2 years. One of the foodstuffs rich in micro and macro nutrients is Moringa leaves. This literature study aims to review the results of research on Moringa leaves as a food ingredient in an effort to prevent stunting during pregnancy and lactation. This research is a type of literature study research by searching on Google Scholar. The results of the study obtained that 5 literatures used stated a significant effect of Moringa leaves in preventing stunting. Moringa leaves can be processed as food that is rich in nutrients in the form of carbohydrates, proteins, fats, vitamins, minerals as an alternative to stunting prevention. Moringa leaves can be processed by extraction, made into flour, ice cream, or made into vegetables. Therefore, it is recommended for pregnant and lactating women to use Moringa leaves as food with high nutritional value.